Acaro del coco, Aceria guerreronis Keifer (Arácnidae: Acari: Eriophyidae) - Forrest W. Howard; Dave Moore; Edwin Abreu; Sergio Gallo (EDIS)
EENY-405, a 7-page illustrated fact sheet by F. W. Howard, Dave Moore, Edwin Abreu, and Sergio Gallo, is part of the Featured Creatures collection, and is the Spanish-language version of EENY-398/IN709: A Coconut Mite, Aceria guerreronis Keifer (Arachnida: Acari: Eriophyidae). It describes one of the worst arthropod pests of coconut palms, which attacks the young fruits and can cause scarring and distortion and premature fruit drop. Includes sections on distribution, description, biology and ecology, hosts, damage and economic importance, detection, management, and selected references. Published by the UF Department of Entomology and Nematology, June 2007.